Clinical features and treatment effect of HIV-associated immune thrombocytopenia—single center Ten-Years data summary. (31st December 2023) - Tan, YaXian; Che, Lei; Bi, Hui; Fan, ShanShan; Zhou, ZePing; Min, HaiYan
Abstract: Thrombocytopenia represents one of the most prevalent hematologic complications observed in patients infected with the human immunodeficiency virus (HIV). In this study, we sought to analyze the clinical characteristics and treatment outcomes of patients with coexisting HIV and thrombocytopenia. Specifically, we retrospectively examined the medical records of 45 patients diagnosed with HIV/AIDS and thrombocytopenia at the Yunnan Infectious Diseases Specialist Hospital between January 2010 and December 2020, all of whom received highly active antiretroviral therapy (HAART) with/without glucocorticoids. The median follow-up period was 79 days, ranging between 14 and 368 days, the total platelet count was higher after receiving treatment than before (Z = −5.662, P  < .001). Among the cohort, 27 patients (60.0%) responded to treatment, with 12 patients (44.44%) experiencing relapse during the follow-up period. The response rate (80.00%) of newly diagnosed ITP were significantly higher than of persistent ITP (28.57%) and chronic ITP (38.46%) ( \x 2  = 9.560, P  = .008) and the relapse rate of the newly diagnosed ITP (30.00%) was significantly lower than the persistent ITP and chronic ITP (100.00%, 80.00%) ( \x 2  = 6.750, P  = .034). Notably, we found that the number of CD4+ T cells, duration of HIV infection, selection of HAART and type of glucocorticoids administered displayed no statistically significant effect on platelet count, treatment response, or relapse rate. However, we observed a significant decrease in platelet count in hepatitis C virus-positive individuals coinfected with HIV compared to those with HIV alone (Z = −2.855, P  = .003). Our findings suggest that patients diagnosed with HIV and thrombocytopenia exhibit a low response rate to treatment and have an increased likelihood of relapse.